Role of 18F-fluoro-2-deoxyglucose positron emission tomography/computed tomography(18F-FDG PET/CT) in malignant ovarian germ cell tumors: a single-center experience with long term follow-up. Issue 8 (30th July 2019) - Dolci, Carlotta; Ceppi, Lorenzo; Guerra, Luca; Crivellaro, Cinzia; Lamanna, Maria; Adorni, Marco; Elisei, Federica; Bonazzi, Cristina Maria; Sina, Federica; Fruscio, Robert; Messa, Cristina
Abstract : Introduction: 18 F-fluoro-2-deoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) is a diagnostic tool widely used in oncology, but to date there are no established recommendations for its use in malignant ovarian germ cell tumors. The aim of this study was to evaluate the role of 18 F-FDG PET/CT in the clinical management of patients with malignant ovarian germ cell tumors. Methods: This was a retrospective review of 18 F-FDG PET/CT scans performed in patients diagnosed with malignant ovarian germ cell tumors treated at the gynecology department of San Gerardo Hospital (Monza, Italy) from June 2006 to December 2016. Data collected included clinical history, radiological, biochemical and pathological evaluation, treatment, follow-up, outcome, and clinical indication for the PET/CT scan. PET/CT findings were categorized as negative/normal (no abnormal FDG uptake or physiological uptake), positive/abnormal (FDG uptake considered to indicate active germ cell malignancy), or equivocal (FDG uptake of uncertain significance, not clearly correlated to neoplastic disease). Results: A total of 69 PET/CT scans in 37 patients were evaluated. The mean age at diagnosis was 25 years (range 20–48). The majority of patients had International Federation of Gynecology and Obstetrics (FIGO) stage I (22/37) disease and had a diagnosis of dysgerminomas (18/37). Imaging indications were initial staging before treatment (4/69, 6%), staging after inadequate staging surgery (24/69, 35%), restaging after adjuvant chemotherapy (17/69, 25%), relapse suspect (9/69, 13%), and follow-up (15/69, 21%). Pathology confirmation of PET/CT results was available in 28/69 (40.5%) studies. All negative PET/CT (15/28) cases were confirmed with laparoscopy as true negative; among 13/28 positive PET cases, histopathology confirmed 7 (54%) as true positive and 6 (46%) as false positive (5 inflammatory and 1 mature teratoma implants). Patient-based analysis showed 100% sensitivity, 71% specificity, 54% positive predictive value, 100% negative predictive value, and 79% accuracy. Clinical follow-up was available in 41 (59.4%) of 69 PET/CT images: 28/41 studies were negative and 13/41 positive. A mean follow-up of 28 months (median 15, range 5–102) confirmed negative PET/CT studies. A total of 13 positive PET/CT patients underwent chemotherapy with subsequent evidence of disease response. Discussion: PET/CT in malignant ovarian germ cell tumors was mainly performed for staging after inadequate staging surgery or for restaging after adjuvant chemotherapy. PET/CT was associated with high sensitivity and negative predictive value.